My friend Tom : the poet-playwright Tennessee Williams - Smith, William Jay, 1918-2015 (University Press of Mississippi, 2012)
Tennessee Williams was one of the most acclaimed, popular, and controversial American playwrights of the twentieth century. In his early years, Williams concentrated his literary talents just as intently on poetry as on plays. Watching over him during this critical learning period was the author of this book, a close friend of Williams, who met Williams in St. Louis as both were embarking on careers as writers. The book is at once the author's critical analysis of Williams's early work, a brief biography of Williams during his development stages as a writer, and a meditation on his friend's career.